Synthesis and mesomorphic properties of new heterocyclic liquidcrystals with Central Ester–Chalcone linkages - Lim, Chery Yong Wei; Ha, Sie Tiong; Yeap, Guan Yeow; Sastry, S. Sreehari (Taylor & Francis, 2017)
A series of new calamitic liquid crystals, 4-[3-(pyridin-4-yl)prop-2-enoyl]phenyl 4-alkyloxybenzoates, comprising a pyridyl core,ester–chalcone central linkage and terminal alkyloxy chain were synthesized and characterized. This series consists of four membersthat differ by the length of the alkyloxy chain (CnH2n+1O , where n = 10, 12, 14, 16). The structures of the title compounds wereelucidated using spectroscopic and spectrometric techniques, such as FT-IR, NMR (1H and13C) and EI-MS. The mesomorphicproperties were studied using differential scanning calorimetry and optical polarizing microscopy. The decyloxy-containing com-pound was found to be non-mesogenic, whilst the compounds containing n-dodecyloxy to n-hexadecyloxy chains exhibited anenantiotropic smectic A phase with a fan-shaped texture. From the structure–property relationship study, it was proposed that thenumber of carbons in the alkyloxy chain must be at least 12 (n ≥ 12) to generate the smectic phase in the corresponding substitutedArCOOArCOCH CHC5H4N compounds.